El incumplimiento del contrato de promesa de compra-venta y la vulneración de los derechos de los contratantes - Ruth Patricia, Ortiz Narváez (2021)
ABSTRACT This research, called “BREACH OF PURCHASE-SALE PROMISE CONTRACT AND VIOLATION OF CONTRACTORS RIGHTS,” presents a systematic and updated approach to contracted obligations in a promise of sale contract. They were relating it to the legal effects that they occur in the event of non-compliance, resulting in the violation of rights and principles described in the Constitution of the Republic of Ecuador, their analysis and development being of vital importance. Regarding the conceptual framework, this research will be divided into three chapters: In chapter I, the purchase-sale promise contract, the historical background, conceptualizations, characteristics, essential requirements, and legal nature will be detailed. In Chapter II, called legal effects of breach of contract, the notarial requirement, the action, the judicial procedure, and the declaration of nullity will be analyzed. Finally, in Chapter III, called violation of the rights and principles of the contracting parties, the right to property, legal certainty, the right to adequate reparation, the right to due process will be described, in the obligation of all judicial authorities to guarantee the right to the parties in due course, the principle of good faith of the contracting parties, the principle of efficiency and the principle of proportionality. KEYWORDS: obligations, contracts, the promise of sale, rights, principles, violation, requirements, legal actions, procedure. Reviewed by: Mgs. Lorena Solis Viteri PROFESSOR C.C.0603356783